Determinants of job mismatch among graduates : a case study of clerical workers at Lahore, Pakistan - Chaudhry, Mumtaz Anwar; Khalid, Rabia; Özcan, Rasim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Job mismatch among graduates reflects inefficiencies in the labor market. An imbalance between the demand and supply of graduates in the labor market leads to a horizontal mismatch. Nations make progress based on knowledge and education but despite obtaining higher education individuals are unable to find a job related to their field of study. This phenomenon occurs when educational institutes produce a large number of graduates while on the other hand, the supply of graduates exceeds the demand for graduates. This study aims to find out the determinants of horizontal mismatch and to analyze the reasons why workers have accepted the mismatched job. By using the worker’s self-assessment method required data is collected from the clerical workers of public and private sector universities at Lahore in 2019. These universities include the University of the Punjab, Lahore, and the University of Management and Technology, Lahore. Results of Logistic Regression analysis concluded that cost of job search, asymmetric information, and methods used to find a job are the most important determinants of job-mismatch. This study has also analyzed the reasons why workers have accepted their present mismatched job. Findings concluded that individuals accepted mismatched-job due to pay and promotion opportunities and a good working environment. This study suggested establishing linkages between educational institutes and industries to better formulate the policy that reduces the extent of horizontal mismatch.